Estrutura populacional do cação-viola, Zapteryx Brevirostris, em um ambiente de ressurgência costeira - Souza, Lilian Glória Xavier de (2015)
The Lesser guitarfish, Zapteryx brevirostris (Müller & Henle, 1841), is considered a vulnerable species. This is due to its low fecundity and because this species is commonly captured as fisheries by-catch. This study compiled data collection three years and described aspects of length, sex ratio, seasonality and bathymetry (30, 45 and 60 m) of a population of Z. brevirostris. 211 specimens were studied, where the population of males and females Z. brevirostris is distributed in practically all classes total length of 30 to 45 m. If there is no segregation of male and female these depths. None of the specimens were found at 60 m. This was the first study of CPUE data Z. brevirostris. This work is the first to explore aspects of the seasonal distribution of the species at depths of 30, 45 and 60 m systematically for three years of sampling.